Species determination in plankton net (20 μm) concentrates by light microscopy during the PHYCOB cruise in the Southwestern Black Sea in 2021 - Nina Dzhembekova; Bernd Krock (PANGAEA, 2024)
At each station two vertical net tows were taken from the water column using a 20 μm plankton net (438-030, Hydro-Bios, Kiel, Germany) for analyses of plankton and phycotoxins. The depth of the hauls was fixed to 0 - 30 m. The collected net tow concentrates were adjusted to 1 L with filtered seawater. 50 mL aliquots were fixed with formaldehyde solution, buffered to pH 8-8.2 with disodiumtetraborate (4% final concentration) for microscopic analyses of phytoplankton. Taxonomic identification and cell counts of the net samples were done under inverted microscope (Nikon Eclipse TE2000-U) connected to a video-interactive image analysis system (L.U.C.I.A, Version 4.8, Laboratory Imaging Ltd, Prague, Czech Republic) at 400 exttimes magnification in Sedgwick-Rafter counting chambers. Only dinoflagellates species and the diatom Pseudo-nitzschia genus were considered during the analyses. 400 cells were counted from each sample, while rare and large species were checked in the whole counting chamber (Moncheva and Parr 2010). Cell abundance was expressed in cells per net tow. Taxonomic nomenclature was according to the on-line data-base of World Register of Marine Species (WoRMS) http://www.marinespecies.org/. The QC/QA of the data was performed following the quality control Guidelines for phytoplankton (Moncheva 2010). IOC-UNESCO Taxonomic Reference List of Harmful Micro Algae was used as a reference database of toxic microalgal species selection.
In: Krock, Bernd; Tillmann, Urban; Möller, Kristof; Koch, Florian; Dursun, Fuat; Boicenco, Laura; Vlas, Oana; Dzhembekova, Nina; Mutlu, Sabri; Aslan, Ertugrul (2024): Data collection of the PHYCOB cruise with focus on harmfula algal species in the Southwestern Black Sea in 2021 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963976